Prawne znaczenie Preambuły do Konstytucji RP z 1997 roku - Banaszak, Bogusław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The article shows the place and meaning of the introduction to the 1997 Constitution in the context of disputes over its normative meaning. This is an important topic of constitutional discussions over the years. Author of this thesis, takes the view that nowadays in democratic countries, the conviction is growing that, regardless of its specificity, the preamble to the constitution is normative. Such a view prevails in current jurisprudence and doctrine, and the normative character of the Preamble of the Constitution of the Republic of Poland from 1997 plays an important role in drawing the interpretation of particular norms of the basic law.
Keywords: normative meaning; preamble; Constitution